2018
DOI: 10.3390/ma11091694
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Diffusion through Enamel and Dentin

Abstract: The purpose of this study was to evaluate the in vitro diffusion of commercial bleaching products (hydrogen peroxide (HP) or carbamide peroxide (CP) based) with different application protocols. Human enamel-dentin discs were obtained and divided into 20 groups. Four commercial products based on HP (Pola Office+(PO), Perfect Bleach (PB), Norblanc Office-automix (NO), and Boost (BT)), and one based on CP (PolaDay CP (PD)), were evaluated with different application protocols (3 applications × 10 min or 1 applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Previous studies evaluated the in vitro diffusion of high (35%–40%) and low (10%) HP concentrations used for different in‐office bleaching protocols and demonstrated that the increasing of the concentration, 16,18 contact time 16,19,26 or the number of bleaching agent applications 39 resulted in greater HP diffusion. It was observed in vitro that the same bleaching gel tested in the current study promoted an increase of approximately 48% and 60% of diffusion rate when it was used for two or three 10 min applications, respectively 39 . These findings could justify the high risk of TS observed in the present study but do not reflect the real conditions observed in vivo, where pulpal pressure and organic components presents in dentinal tubules could decrease the negative effects of bleaching agent on dental pulp 18 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluated the in vitro diffusion of high (35%–40%) and low (10%) HP concentrations used for different in‐office bleaching protocols and demonstrated that the increasing of the concentration, 16,18 contact time 16,19,26 or the number of bleaching agent applications 39 resulted in greater HP diffusion. It was observed in vitro that the same bleaching gel tested in the current study promoted an increase of approximately 48% and 60% of diffusion rate when it was used for two or three 10 min applications, respectively 39 . These findings could justify the high risk of TS observed in the present study but do not reflect the real conditions observed in vivo, where pulpal pressure and organic components presents in dentinal tubules could decrease the negative effects of bleaching agent on dental pulp 18 …”
Section: Discussionmentioning
confidence: 99%
“…Only after having performed the scaling is it possible to proceed with the actual whitening. Bleaching involves a chemical reaction of oxidation-reduction, in which the tooth goes against oxidation, also oxidizing all the pigments present on the enamel, and reducing the whitening material (Figure 2) [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the most important properties of a whitening product are the degree of diffusion through tooth structure and the ability to react with chromophore molecules. The selection of a bleaching product depends not only on efficacy, release rate, or the potential to cause damage to surrounding structures, but also on the differential diagnosis of tooth discoloration and the choice of technique [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%